2005
DOI: 10.2337/diacare.28.6.1410
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adiponectin Is Increased in Type 1 Diabetic Patients With Nephropathy

Abstract: OBJECTIVE -To elucidate whether serum adiponectin is associated with renal function, low-grade inflammatory markers, metabolic control, and insulin resistance in type 1 diabetic patients with and without nephropathy. RESEARCH DESIGN AND METHODS-A total of 189 type 1 diabetic patients from the Finnish Diabetic Nephropathy Study were divided into three groups based on their urinary albumin excretion rate (AER): patients with normal AER (n ϭ 66) had no antihypertensive medication, while patients with microalbumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
92
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 33 publications
18
92
4
Order By: Relevance
“…Previous cross-sectional studies in adults with type 1 diabetes have shown a variable relationship between adiponectin levels and glycaemic control, with a negative [1], a positive [11] or no correlation at all [13]. In these studies, differences between the sexes were either not found or not reported.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Previous cross-sectional studies in adults with type 1 diabetes have shown a variable relationship between adiponectin levels and glycaemic control, with a negative [1], a positive [11] or no correlation at all [13]. In these studies, differences between the sexes were either not found or not reported.…”
Section: Discussionmentioning
confidence: 57%
“…However, testing for interaction with sex supported these discordant observations. In addition, higher adiponectin levels in adults have been found in association with reduced glomerular filtration rate, suggesting reduced clearance of adiponectin [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma adiponectin was determined by an in-house timeresolved immunofluorometric assay (TR-IFMA) based on commercial antibodies and recombinant human adiponectin (R&D Systems, Abingdon, UK) as recently described [33]. Adiponectin has a molecular mass of ∼30-36 kDa depending on the degree of glycosylation, but the molecule is known to form a wide range of polymers in vivo.…”
Section: Assaysmentioning
confidence: 99%
“…However, an increase in circulating adiponectin is found in patients with kidney diseases [11][12][13]. Polymorphisms in the two small regions of ADIPOQ, one in the promoter and another in the boundary of exon 2-intron 2, are the most commonly discussed variants.…”
Section: Introductionmentioning
confidence: 99%